MULTIFACETED FINANCIAL DEVELOPMENT AND ECONOMIC GROWTH: BOOTSTRAP PANEL CAUSALITY APPROACH - ŞEN, Sedef (Akademik Hassasiyetler, 2023)
A large body of both theoretical and empirical literature has been conducted to show the relationship between financial development (or called financial depth) and economic growth. However, for Central Europe and Baltic countries, the existing empirical evidence is scarce. This paper revisits whether financial development stimulates economic growth in the context of eleven Central Europe and Baltic countries during the 2000-2019 period. By incorporating broad characteristics of financial institutions (such as banks and insurance companies) and financial markets (including stock markets, bond markets, and derivative markets) into the finance-growth nexus, this paper not only attempts to underline the potential importance of financial depth for economic growth but also tests the hypothesis that financial access, efficiency, and stability promote economic growth or vice versa. This paper applies a panel bootstrap approach to Granger causality testing, which considers cross-sectional dependence and heterogeneity issues. Empirical results show limited support for the supply-leading and demand following hypotheses.
Keywords: Financial Development; Economic Growth; Panel Causality; 8. Economic growth; 1. No poverty